PENGARUH ASAM HUMAT-BIOCHAR DAN PUPUK SP-36 TERHADAP KETERSEDIAAN HARA P, SERAPAN P, PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI HIJAU PADA ULTISOL - Wanitri, Ratih Indah; Hermawan, Agus; Safani, Nabila Putri; Prayitno , Muh. Bambang (AGRICA, 2025)
Ultisol soils have low fertility, characterized by high acidity, low C-organic content and limited availability of P nutrients. One way to improve the properties of Ultisol is through the application of a combination of humic acid-biochar and SP-36 fertilizer. This study aims to evaluate the effect of the combination on phosphorus availability, as well as the growth and yield of mustard greens (Brassica juncea L.) grown on Ultisol. The research was conducted in the Plastic House, Faculty of Agriculture, Sriwijaya University, from September to December 2024. The method used was a Randomized Complete Factorial Design (RALF) with two treatment factors, namely humic acid-biochar (A) with 4 levels and SP-36 fertilizer (P) with 3 levels. Each treatment combination was repeated three times, resulting in a total of 36 experimental units. The results showed that the application of humic acid-biochar at a dose of 20 tons ha-¹ gave an increase in soil pH, C-organic content, phosphorus availability, phosphorus uptake, and growth and yield of green mustard plants compared to other doses. Meanwhile, the application of SP-36 fertilizer at a dose of 100 kg ha-¹ also increased soil pH, phosphorus availability and uptake, as well as the growth and production of mustard greens. In addition, there was a significant interaction between humic acid-biochar treatment and SP-36 fertilizer on plant height and wet weight of mustard greens.